(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Anaemia is the commonest nutritional problem in the world but the burden of anaemia is disproportionately borne among children in developing countries. Physical, mental and social developments of the children are adversely affected by childhood anaemia. Objective: To assess the prevalence and severity of anaemia based on haemoglobin levels in children less than five years of age attending in Combined Military Hospital (CMH), Sylhet. Materials and Methods: This cross sectional study was conducted at CMH, Sylhet from January 2018 to December 2018. The study included 184 children aged 6 months to less than 5 years. Personal data and history of co-existing medical conditions were collected by data collection sheet and then analyzed. Results: The prevalence of anaemia was 74(40.2%). Out of the anaemic under five children, 46 (75.7%) had mild anaemia, 18(24.3%) had moderate anaemia, and no one had severe anaemia (WHO definition). There was no significant difference for prevalence of anaemia in relation to sex and age different groups. Conclusion: The prevalence of anaemia in 6 months to less than 5 years children was found to be high, given the negative impact of anaemia on the development of children in future, so there is an urgent need for effective and efficient remedial health interventions. JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 76-79